Heritage and Identity in Art-Based Educational Research from a Multimodal Approach - Álvarez-Rodríguez, Dolores; Bajardi, Alice (Arte, Individuo y Sociedad, 2016)
This paper describes two interconnected and related research experiences, the first one developed in 2007 was the CALVINO Project by the Culture 2000 Program of the European Union, and the second one was implemented during 2014 as part of Research an Innovation Project in Secondary Education in Andalusia (PIIISA). Both projects have in common the topic of identity from an idea of heritage and the fact that in both cases has been implemented art-based research methodologies within a multimodal approach. From these two anchor points about the subject matter (what) and the methodology (how) we analyze them to obtain relevant conclusions that, on the one hand, value these significant practical and, on other hand, provide expertise for future research proposals following the same topic and/or methodology. propuestas de investigación en el ámbito temático y/o metodológico.